Problematika dan Solusi Kesehatan Reproduksi Remaja Perspektif Fikih dan Psiko-Sosiologis - Durotun Nafisah; Khoirul Amru Harahap (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
This paper examines the problems of Reproductive Health from fiqh and psycho sociological perspectives. At the end of the article, the author offers a solution to this problem. This research is literature and uses mixed theory with field studies as the sample. The research findings are that in the perspective of thoharoh fiqh, the problem is about water as a medium for purification from hadas and uncleanness, baligh, istinja’, ablution and bathing. Meanwhile, in the psycho-sociological perspective, they do not know basic knowledge about Kespro, sexual desire, shame to convey it to parents, feelings of discomfort and guilt about these desires. The solution to this problem is that Kespro is made a compulsory subject at the professional level or an integral part of the fiqh course, especially on the theme of thoharoh, it is necessary to conduct periodic studies on Kespro and or form an institution that handles the problems of Pros, namely the Adolescent Reproductive Health Information Center (PIKER).